2022
DOI: 10.18502/ijm.v14i1.8806
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Staphylococcus aureus isolates from pastry samples by rep-PCR and phage typing

Abstract: Background and Objectives: Staphylococcus aureus is one of the most common causes of food poisoning. This study aimed to identify S. aureus isolated from pastries, the virulence factors, antimicrobial resistance patterns, biofilm formation, and then classification based on SCCmec types, phage types, and also Rep types. Materials and Methods: In this study, 370 creamy and dried pastry samples have been randomly collected from different confectioneries in Hamadan city. The S. aureus isolates were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…Our results identified that 16.24 and 33 percent of workers' nasal and creamy pastries were contaminated with S. aureus , respectively. Other studies in Iran have been revealed that approximately 20 to 30 percent of creamy pastries contaminated with this pathogen ( 12 , 13 ). Sami et al (2013) showed that 20 percent of the cream-filled sweets offered in the confectioneries of Kerman were contaminated with S. aureus ( 14 ).…”
Section: Discussionmentioning
confidence: 95%
“…Our results identified that 16.24 and 33 percent of workers' nasal and creamy pastries were contaminated with S. aureus , respectively. Other studies in Iran have been revealed that approximately 20 to 30 percent of creamy pastries contaminated with this pathogen ( 12 , 13 ). Sami et al (2013) showed that 20 percent of the cream-filled sweets offered in the confectioneries of Kerman were contaminated with S. aureus ( 14 ).…”
Section: Discussionmentioning
confidence: 95%
“…The rep-PCR was performed according to the protocol of Arabestani el al. [38]. Phylogenetic group analysis for all isolates was accomplished based on electrophoresis results and isolates were classified into different groups.…”
Section: Genotyping By Repetitive Extragenic Palindromic-pcr (Rep-pcr)mentioning
confidence: 99%
“…Finally, different studies have examined the effects of extracts on the quorum-sensing systems of various bacteria and also the prevalence of virulence genes of different bacteria (Arabestani et al, 2022;Dadgar et al, 2014;Kamarehei et al, 2020;Kavyani et al, 2019;Nouri et al, 2022;Vaziriamjad et al, 2022) Therefore, in this study, the potential of some natural agents was investigated on the biofilm-promoting property of S. mutans. These natural agents exerted considerable biological effects and could protect the teeth from the injuries caused by S. mutans.…”
Section: Anti-biofilm Effects Of Piperine On S Mutansmentioning
confidence: 99%
“…Finally, different studies have examined the effects of extracts on the quorum‐sensing systems of various bacteria and also the prevalence of virulence genes of different bacteria (Arabestani et al, 2022 ; Dadgar et al, 2014 ; Kamarehei et al, 2020 ; Kavyani et al, 2019 ; Nouri et al, 2022 ; Vaziriamjad et al, 2022 ). The properties and the antibacterial effects of different natural compounds against S. mutans are presented in Table 1 .…”
Section: Introductionmentioning
confidence: 99%